Shame is valuable - Euvrard, Jonathan George (Rhodes University, Faculty of Humanities, Department of Philosophy, 2009)
In this thesis I argue that shame is valuable because it contributes to the moral life by promoting coherence. I start by developing and defending a conception of shame. On my conception, rational shame involves a negative self-assessment, in which I am both the assessor and the object of assessment, and in which the standard of assessment is my own. I then develop a notion of coherence, and apply it to the relationship between values, and the relationship between values and actions. I also tie the notion of coherence to what I call "the moral life" . I then discuss two ways in which shame can work to promote coherence. Firstly, I describe a process of critical reflective self-assessment, and show how this is a particularly effective method of promoting coherence when coupled with shame. Secondly, I discuss the connection between my emotions and my values, arguing that this connection promotes coherence, and that shame works to reinforce this connection and thereby to promote coherence.
Keywords: Shame; Ethics; Self-evaluation